A Therapeutic Strategy for All Pneumonia Patients: A 3-Year Prospective Multicenter Cohort Study Using Risk Factors for Multidrug-resistant Pathogens to Select Initial Empiric Therapy. (1st August 2018) - Maruyama, Takaya; Fujisawa, Takao; Ishida, Tadashi; Ito, Akihiro; Oyamada, Yoshitaka; Fujimoto, Kazuyuki; Yoshida, Masamichi; Maeda, Hikaru; Miyashita, Naoyuki; Nagai, Hideaki; Imamura, Yoshifumi; Shime, Nobuaki; et al.
Abstract: Background: Empiric therapy of pneumonia is currently based on the site of acquisition (community or hospital), but could be chosen, based on risk factors for multidrug-resistant (MDR) pathogens, independent of site of acquisition. Methods: We prospectively applied a therapeutic algorithm based on MDR risks, in a multicenter cohort study of 1089 patients with 656 community-acquired pneumonia (CAP), 238 healthcare-associated pneumonia (HCAP), 140 hospital-acquired pneumonia (HAP), or 55 ventilator-associated pneumonia (VAP). Results: Approximately 83% of patients were treated according to the algorithm, with 4.3% receiving inappropriate therapy. The frequency of MDR pathogens varied, respectively, with VAP (50.9%), HAP (27.9%), HCAP (10.9%), and CAP (5.2%). Those with ≥2 MDR risks had MDR pathogens more often than those with 0–1 MDR risk (25.8% vs 5.3%, P < .001). The 30-day mortality rates were as follows: VAP (18.2%), HAP (13.6%), HCAP (6.7%), and CAP (4.7%), and were lower in patients with 0–1 MDR risks than in those with ≥2 MDR risks (4.5% vs 12.5%, P < .001). In multivariate logistic regression analysis, 5 risk factors (advanced age, hematocrit <30%, malnutrition, dehydration, and chronic liver disease), as well as hypotension and inappropriate therapy were significantly correlated with 30-day mortality, whereas the classification of pneumonia type (VAP, HAP, HCAP, CAP) was not. Conclusions: Individual MDR risk factors can be used in a unified algorithm to guide and simplify empiric therapy for all pneumonia patients, and were more important than the classification of site of pneumonia acquisition in determining 30-day mortality. Clinical Trials Registration: JMA-IIA00146. Abstract : We applied a single algorithm to all forms of pneumonia, which was followed in 82.5% of a cohort of 1089 patients. Only 4.3% received inappropriate therapy; in multivariate analysis, site of pneumonia acquisition was not predictive of 30-day mortality.